Inflammatory and immune responses to a 3-day period of downhill running in active females - Jafariyan, S.; Monazzami, A.; Nikousefat, Z.; Nobahar, M.; Yari, K. (Cellular and Molecular Biology, 2017)
Exercise-induced muscle damage (EIMD) is accompanied by inflammatory and immune responses. However, due to the repeated bout effect, there will probably be less EIMD. Hence, the purpose was to investigate inflammatory and immune responses over a three-day period of downhill running in active females. Eleven moderately trained healthy females performed three 60-minute bouts of downhill running in -13.5% grade, separated by 24 hours, at a speed eliciting 70–80% of their VO2peak on level grade. Delayed onset muscle soreness (DOMS), range of motion (ROM) and maximum knee isotonic strength (1RM) were measured pre- and two-hour post every bout. Blood variables, including CBC, serum lactate dehydrogenase (LDH), creatine kinase (CK), myoglobin (Mb), IL-10, IL-6 and Monocyte chemoattractant protein-1 (MCP-1) were measured at 1 hour before the first bout and two hours after every bout. Data was analysed by repeated measure ANOVA (P<0.05). Although CK, LDH, Mb, IL-10, IL-6, MCP-1, total leukocyte count, monocytes and neutrophils increased significantly following the first bout, CK, LDH, Mb, IL-10, monocytes and neutrophils were only significantly higher following the third bout compared to the baseline (all P<0.05). Moreover, IL-10 and IL-6 decreased following the second and third bouts compared to the first bout (P<0.05). In comparison with the baseline, lymphocytes decreased after the second bout, DOMS increased following the second and third bouts, 1RM decreased following the first and second bouts (all P<0.05). ROM showed no significant difference. The three-day period of downhill running did not exacerbate EIMD and inflammatory response was partly attenuated.